SISTEM AKUNTANSI PENGELUARAN KAS PADA PT LINTAS SAMUDRA JAYA - Rika Yuliastuti; Aini, Nur (Ekomania, 2023)
Cash is a company balance that comes from company profits or comes from company capital in order to meet the company's needs. Cash comes from cash balances and checking accounts. Cash flow statements are divided into two types, namely cash inflows and cash outflows. Cash inflow is the flow of cash flow due to transactions and can generate profits. Cash outflow is the flow of cash flows that occur due to carrying out various transactions and resulting in expenses and cash disbursements in the company. Cash disbursements can occur because of expenses for employee salaries, and expenses for the company. Cash disbursements in accounting have four basic activities, namely ordering, receiving, approving supplier invoices, and cash disbursements. The research method used today uses qualitative research methods. Where the research method used at this time using the method of description of the documentation obtained directly from the field. The method used for data collection is direct observation or observation, direct interview and documentation. The cash disbursement process at PT Lintas Samudra Jaya is usually also carried out by other companies. Transactions carried out at the company are usually also for paying several vendors, paying employee salaries, paying escort fees, paying taxes, and other costs. The use of documents in the outgoing accounting system at PT Lintas Samudra Jaya are Vouchers, Invoices, Receipts, and Cash Out Evidence. The accounting records used at PT Lintas Samudra Jaya use a manual cash disbursement accounting system every day and is accompanied by evidence. There is an internal control tasked with being a supervisor in the system so that it can be in accordance with what is expected to prevent misappropriation of funds.